A conceptual framework for integrating Human-Centred AI in 2D animation education: the 2DTAP model - Ramlie, Mohd Khairulnizam (Universiti Teknologi MARA, Perak, 2025)
The 2D animation course at higher education institutions demands students to acquire both technical and creative skills within a limited time frame. However, pre-production phases such as idea generation, scriptwriting, and visual development often consume up to 40% of the semester, thus reducing time available for mastering complex animation production techniques. This study introduces the 2D Animation Proposal Development Model (2DTAP), a pedagogical innovation that integrates Artificial Intelligence (AI) with a Human-Centred Artificial Intelligence (HCAI) framework. The model is designed to accelerate and simplify the pre-production process without compromising students’ creativity and autonomy. By emphasizing principles such as augmentation, human-centric design, transparency, and student control over AI tools, 2DTAP enables students to produce higher-quality, consistent, and industry-relevant project proposals. This paper critically discusses how 2DTAP strengthens project-based learning in animation through ethical, interactive, and adaptive strategies that foster creativity and reflective thinking. The findings of this study are expected to contribute toward the development of a more responsive animation curriculum aligned with the challenges of future digital creative education